Employment programs for food security in Sub-Saharan Africa - Teklu, Tesfaye (International Food Policy Research Institute, 1995)
Employment programs, particularly labor-intensive public works (LIPW), have a long history in Sub-Saharan Africa, dating back to the 1960s. The programs expanded rapidly in the 1980s and early 1990s, especially in countries that experienced sharp declines in employment and real wages. Labor-intensive public works have the potential to serve as both short-term sources of employment and long-term generators of growth and productivity increases. They can be designed cost-effectively to alleviate poverty and improve food security. This function can be further strengthened if they are combined with other food-security-enhancing policies and projects. Policymakers, donors, and researchers need to pay close attention to improving the design of public works and to searching for the right portfolio of intervention instruments.